Az egyetemi élet átolitizálódásának megnyilvánulása 1939-ben Debrecenben – hallgatói feljelentés Tankó Béla ellen és Hóman Bálint levele - Mudrák, József; Király, Sándor (Gerundium, 2018)
The Appearance of the Politicization of the University Life in Debrecen in 1939. A student’s Accusation against Béla Tankó and Bálint Hóman’s response. A very special source of the history of the Hungarian higher education and of the history of the University of Debrecen that accusation which was made in the autumn of 1939 by a student. This short and nameless letter was an accusation against professor Béla Tankó who had taken a note about the German origin of Bálint Hóman who was the Secretary of Religion and Public Education at that time. One of the students who was the member of the Árpád Comradeship Association wrote a short and modest letter to Hóman about it. This was a clear sign of the radicalization and the politicization of the whole society and of the life in the Hungarian universities. Also had been found the response of Bálint Hóman who sent back this accusation to Béla Tankó with a short letter in which he interpreted this as a wrong deliver. This unpleasant case had been solved by Hóman this way, but the radicalization of the students of the universities and the devaluation of the Hungarian political culture continued.